ORGANIZATION OF THE PRODUCTION MANAGEMENT SYSTEM IN ENTERPRISES ON THE BASIS OF NEW TECHNOLOGIES - Umida Moʻminjonova Abdurazoq qizi; S.Dilli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article explores the organization of production management systems in enterprises using new technologies. It discusses the significance of implementing advanced technologies in production processes and highlights the benefits they bring to overall organizational efficiency. The article provides insights into the methods employed in integrating new technologies, presents the results of adopting such systems, and discusses their implications. Finally, it concludes with suggestions for further improvement and future directions in the field of production management systems.